5 - Family Structure, Race, Gender and Poverty: The Case of Food Deprivation in South Africa - Acheampong Yaw Amoateng; Boitumelo Marilyn Patience Setlalentoa (African Sociological Review, 2015)
This study sought to examine the relationship between race, family structure and gender on one hand, and food deprivation as a measure of poverty on the other hand in South Africa. Main effects were found for race, residence, presence of children and adults, while interaction effect was found for race and family structure. Whites, and to a large extent Indians/Asians, were less likely to experience food deprivation, while black Africans and coloureds were most likely to experience food deprivation. Couple-headed households were the least likely to experience food deprivation, compared to households headed by either male or female. Finally, the presence of children and the elderly in a household was negatively associated with food deprivation, a finding which supports the view that most poor families in the country depend on social grants to children and the elderly for survival.